Defeitos de desenvolvimento de esmalte e cárie dentária em dentes decíduos: uma abordagem multinível - Suzane Paixão Gonçalves (2017)
Dental caries is one of the most prevalent oral diseases in childhood and may be associated with the presence of enamel defects. The objective of this study was to verify if enamel defects are risk factors for dental caries in deciduous teeth of preschool children after an average time of 26 months of follow-up. For this prospective cohort study, a sample calculation was performed and 339 children (113 exposed and226 non-exposed) from 2 to 5 years at baseline (first examination) were sampled. After the mean period of 26 months the same children were examined (second examination-follow-up). The final sample consisted of 325 children, who were divided into two groups according to the exposition. The DDE was diagnosed through the DDE Index. All teeth were examined for caries diagnosis according to World Health Organization (WHO) recommendations and oral hygiene was evaluated and interviews with parents were carried out. Descriptive analyzes were performed and data were analyzed using multiple Poisson regression with multilevel approach, since the teeth (first level, at which the outcome was measured and for which) are grouped into children (second level). This strategy allowed to estimate the effect of different types of DDE on the incidence of dental caries in deciduous teeth, calculating relativerisks (RR) and the respective 95% confidence intervals (CI 95%) adjusted by the other dental and child explanatory variables. Through the multilevel analysis it was observed that DDE is a risk factor for caries (RR: 1.98; 95% CI: 1.20-3.26). In addition, posterior and superior teeth presented a higher risk of developing carious lesions (RR 2.90, 95% CI: 2.45-3.44, RR 1.52, 95% CI: 1.29-1.79, respectively).Among the variables of the child, only ceo-d was associated with the incidence of caries (RR 1.38, 95% CI: 1.31-1.45). Therefore it is concluded that hypoplasia is a risk factor for dental caries in deciduous teeth.